Nursery evaluation of mulberry germplasm (Morus spp.) for growth attributes - Mithilasri, M.; Parthiban, K.T. (Indian Journal of Agroforestry, 2021)
An experiment was carried out with 29 mulberry accessions along with a check variety (V1) at Forest College and Research Institute, Mettupalayam during 2019- 2020. The cuttings from the accessions were evaluated for various growth attributes viz., sprouting (%), rooting (%), survival (%), number of roots cuttings-1, root length, shoot length, number of leaves cuttings-1 and leaf area. Result showed that sprouting percentage varied significantly from 49.52±2.27% (ME-0006) to 98.95±1.44% (MI-0364). The maximum vigour index was registered in MI-0718 (1820±7.46%) and minimum in ME-0110 (255±1.24%). The higher rooting percentage (93±0.57% in MI-0768) positioned in group a and the lowest rooting percentage (15±0.37% in ME-0110) positioned in group e, were significantly different in terms of statistics (p≤0.05) using Duncan’s LSD post hoc test. Among 29 accessions, 20 accessions viz., ME-0025, MI-0211, MI-0017, MI-0663, MI-0034, MI-0685, ME-0001, ME-0109, MI-0013, MI-0349, MI-0395, MI-0536, MI-0615, MI-0718, MI-0768, ME-0006, MI-0807, MI-0845, ME-0220 and ME-0095 performed better which indicated that the accessions could be deployed for assessment of growth and development for future breeding programme.